The role of the foreign assets in the economy of Ukraine at the turn of the XXth century - Lantukh, I. (Економічний вісник Донбасу, 2016)
The article proves the effectiveness of foreign assets at traction to the domestic investment enterprise at the end of the 19th c. The author determines attractiveness of the domestic business, which was being modernized during the factory-and-plant industrialization and required strong financial donors, for foreign direct investments. Attention is paid to the monetary reform of 1895-1897, which facilitated the process of foreign capital penetration to the domestic market. Also, a parallel is drawn with the modern foreign direct investments to Ukraine and their vectors are analysed. У статті обґрунтовується ефективність залучення іноземних капіталів щодо вітчизняного інвестування підприємництва в кінці ХІХ ст. Автор з'ясовує привабливість вітчизняного підприємництва для прямих іноземних інвестицій, яке модернізувалося в період фабрично-заводської індустріалізації і вимагало потужних фінансових донорів. Звернено увагу на грошову реформу 1895-1897 рр., що полегшала проникнення іноземного капіталу на внутрішній ринок країни. Проводиться також паралель із сучасними прямими іноземними інвестиціями в Українута аналізується їх спрямованість. В статье обосновывается эффективность привлечения иностранных капиталов, относительно отечественного инвестирования предпринимательства в конце ХІХ в. Автор выясняет привлекательность отечественного предпринимательства для прямых иностранных инвестиций, которое модернизировалось в период фабрично-заводской индустриализации и требовало мощных финансовых доноров. Обращено внимание на денежную реформу 1895-1897 гг., которая облегчила проникновение иностранного капитала на внутренний рынок страны. Проводится также параллель с современными прямыми иностранными инвестициями в Украину и анализируется их направленность.